Partial replication in the database state machine - Sousa, António Luís Pinto Ferreira de (2001)
This paper investigates the use of partial replication in the Database State Machine approach introduced ear- lier for fully replicated databases. It builds on the or- der and atomicity properties of group communication primitives to achieve strong consistency and proposes two new abstractions: Resilient Atomic Commit and Fast Atomic Broadcast. Even with atomic broadcast, partial replication re- quires a termination protocol such as atomic commit to ensure transaction atomicity. With Resilient Atomic Commit our termination protocol allows the commit of a transaction despite the failure of some of the par- ticipants. Preliminary performance studies suggest that the additional cost of supporting partial replica- tion can be mitigated through the use of Fast Atomic Broadcast.